(untitled) (Journal of Comparative & International Higher Education, 2024)
As technology integration advances, higher education institutions (HEIs) are experiencing varying degrees of digitalization of their systems, processes and services. This qualitative study explores the status of technology integration and the digital infrastructure of five higher education institutions within the Caribbean. It seeks to answer three questions: i) what is the level of digitization in the institutions’ systems? ii) what is the status of technology integration in the teaching-learning processes in the institutions? iii) what types of digital infrastructures are in place to support the institutional functions? The analysis of the data reveals advances in the digitalization of a number of areas including communication processes, administrative processes, the student life cycle processes and in teaching and learning. This study provides important insights into the evolving landscape of digitalization of higher education within the Caribbean, and should serve to inform policy and practice in this important area.